Measures of acromiohumeral distance with wireless ultrasound machine in subacromial impingement syndrome: an inter-machine reliability study - Dede Burak Tayyip; Aytekin Ebru; Bağcier Fatih (Journal of Ultrasonography)
Shoulder pain is the third most prevalent musculoskeletal condition that impairs function. Subacromial impingement syndrome is among the most typical causes of shoulder pain. The aim of this study was to evaluate inter-machine reliability of acromiohumeral distance measurements performed with standard ultrasound and wireless ultrasound devices in patients with subacromial impingement syndrome.